Penentuan kadar xanton total pada ekstrak alkohol kulit buah tanaman manggis (Garcinia mangostana. L) - Yulianis, Yulianis; Dachriyanus, Dachriyanus; Pramana, Pramana (Tropharm (Trobosan Pharmacy); Vol 1 No 1 (2015): Tropharm (Trobosan Pharmacy), 2021)
Xanthon also useful as free radical scevengers and is also useful as an anticancer. Phase begins with sample preparation, extraction of mangosteen rind, Determination of total xanton, Maximum Wavelength Determination, Making Xanton calibration curve (Î±-mangostin) in ethanol solvent. The results obtained of the mangosteen fruit rind extracts of mangosteen with a yield of 0.7%, the determination of the maximum absorption wavelength of the reference solution Î± mangostin 243 nm, measurement calibration curve Î± mangostin reference solution to the equation regression y = 0.02604 + 0.26839 x and r = 0.998, Xanton determination of compounds from mangosteen peel extract solution that is equal to 0.216% w / w. The sample ripe mangosteen rind has a total concentration of 0.216% xanton b/b.